Pengaruh Profitabilitas Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Komite Audit Sebagai Variable Moderasi - Budiharjo, Roy; Bintara, Rista; Handayani, Riaty; Budyastuti, Triyani; Fitria, Giawan Nur; Dirman, Angela (Lembaga Publikasi Ilmiah Nusantara, 2023)
This study aims to analyze the effect of profitability and company size on company value, with the audit committee as a moderating variable in infrastructure companies listed on the Indonesia Stock Exchange during the period 2018–2021. The population consists of infrastructure companies listed within the observation period, and the sample was selected using purposive sampling. Secondary data were collected through documentation of annual financial reports. The data analysis employed multiple linear regression, preceded by classical assumption tests, while hypothesis testing was conducted using t-tests. The results indicate that profitability and company size have a positive effect on company value. However, the audit committee was unable to moderate the relationship between profitability and company size on company value. These findings highlight the importance of financial performance and firm scale in increasing company value, while the moderating role of the audit committee remains limited.